ANALYSIS OF THE ECONOMIC AND SOCIAL VISIBILITY OF THE CONSTRUCTION OF SIMPLE HOUSES IN EAST JAVA COMMUNITIES (CASE STUDY OF BANGKALAN REGENCY, MADURA) - Putri, Helsa Ade Ayu Kumala; Patriadi, Andi; Sajiyo, Sajiyo (International Journal of Social Service and Research, 2025)
This study explores the perspectives of developers and residents regarding the economic and social visibility of simple housing construction in Bangkalan Regency, East Java. The study seeks to assess the visibility of affordable housing prices and analyze the social conditions associated with simple housing. The results indicate that there is a gap between reality and community expectations of housing adjacent to industrial sites in increasing employment opportunities for the surrounding community. Public transportation, educational facilities, healthcare services, and proximity to employment centers must be incorporated into housing planning to create sustainable and livable communities that meet both the expectations and realities of low-income populations. In addition, the authors developed indicators for the visibility analysis of simple residential buildings in Bang Kalan regency. This research is expected to provide insights into housing affordability and its impact on the social dynamics of the region.